2014
DOI: 10.4236/fns.2014.51004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High Pressure Homogenization (HPH) Treatment on the Nutritional Quality of Egg/Yogurt, Vegetable and Fruit Based Creams

Abstract: The food industry has made large investments in processing facilities relying mostly on conventional thermal processing technologies with well-established reliability and efficacy. These techniques have important disadvantages such as off flavors, destruction of nutrients, and other losses of product quality. Non thermal processing is a key factor for preserving or improving the nutritional value of food, and high pressure homogenization (HPH) processing is now a celebrated option experiencing worldwide commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Conjugated dienes represent the primary oxidation products generated in food systems due to the breakdown of fatty acids. The current data is in line with the conclusion obtained by De Nunzio et al [61] that concentration of conjugated dienes was affected by the processing conditions. Estimation of vitamin A and E was done in this study due to their nutritional and antioxidant perspectives in milk and dairy products.…”
Section: Discussionsupporting
confidence: 93%
“…Conjugated dienes represent the primary oxidation products generated in food systems due to the breakdown of fatty acids. The current data is in line with the conclusion obtained by De Nunzio et al [61] that concentration of conjugated dienes was affected by the processing conditions. Estimation of vitamin A and E was done in this study due to their nutritional and antioxidant perspectives in milk and dairy products.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, several studies reported the ability of HPH to increase the nutritional quality of a wide range of foods [29,30]. For example, Di Nunzio et al [31] reported that HPH improves the nutritional quality of plant food, while the effect on antioxidant and vitamin availability depended on the food matrix. Benjamin and Gamrasni [32] also reported that pomegranate juice treated with HPH had a higher antioxidant value and TPC levels than untreated juice.…”
Section: Microbiological Quality and Phmentioning
confidence: 99%
“…Among these novel technologies, treatments involving high pressure have been rapidly implemented in the food industry (Jermann et al., ; Nunzio et al., ). However, this review will discuss continuous and discontinuous high‐pressure technologies, specifically batch HPTS and continuous UHPH with combined sterilization.…”
Section: Introductionmentioning
confidence: 99%